OREGON TAX INITIATIVE - MCADAM, BOB (Tufts Archival Research Center, 2007)
CONFIDENTIAL; Memorandum to the Tobacco Institute Management Committee from Bob McAdam regarding the Oregon Tax Initiative. Summarizes failed Oregon Tax Initiative in 1990. Examines proposed tax initiative for the following year by the medical and health communities and the coalitions organized around this effort.